The Influence of Service Quality and Customer Value on Grab Customer Satisfaction in Singaraja District - H. G Satria; N. M. D. A. Mayasari (Lembaga Riset dan Inovasi Al-Matani, 2025)
This study aims to provide empirical evidence regarding the influence of service quality and customer value on customer satisfaction, both individually and simultaneously. The approach used in this study is quantitative with a causal research type. 110 Grab customers in Singaraja District were sampled through a purposive sampling method. Data collection was carried out using a Likert scale questionnaire, and the data were analyzed using multiple linear regression techniques with the help of SPSS software version 25.0 for Windows. The results of the analysis show that: (1) service quality has a positive and significant effect on GRAB customer satisfaction in Singaraja District. (2) customer value has a positive and significant effect on GRAB customer satisfaction in Singaraja District. (3) service quality and customer value have a positive and significant effect on GRAB customer satisfaction in Singaraja District. These findings emphasize the need to continue improving aspects of service quality and customer value in order to maintain and increase customer satisfaction, especially in the Singaraja District area. In terms of service quality, Grab is expected to be more consistent in serving customers professionally.